HUBUNGAN PEMBERIAN ANTIBIOTIK PROFILASKSIS DENGAN HUBUNGAN INFEKSI SALURAN KEMIH BERULANG PADA ANAK - , PUNGKY ARDANY K.; , Prof. dr. Sunartini, SpA(K), Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background:Â  RecentÂ  studiesÂ  reportedÂ  aÂ  correlationÂ  betweenÂ  recurrentÂ  urinaryÂ  tractÂ infectionÂ (UTI)Â andÂ theÂ presenceÂ ofÂ renalÂ fibrosis,Â whichÂ mayÂ leadÂ toÂ theÂ developmentÂ ofÂ endâstageÂ renalÂ failure.Â TheÂ administrationÂ ofÂ prophylacticÂ antibioticsÂ toÂ reduceÂ theÂ riskÂ ofÂ theÂ developmentÂ ofÂ recurrentÂ UTIÂ remainsÂ aÂ subjectÂ ofÂ controversy.Â Objectives:Â ToÂ determineÂ whetherÂ thereÂ isÂ aÂ correlationÂ betweenÂ prophylacticÂ antibioticÂ administrationÂ andÂ theÂ incidenceÂ ofÂ recurrentÂ UTIÂ inÂ children.Â Methods:Â  AÂ  caseâcontrolÂ  studyÂ  involvingÂ  consecutivelyâselectedÂ  pediatricÂ  casesÂ  (<Â  18Â years)Â withÂ recurrentÂ UTIÂ wasÂ conducted.Â ChiâsquareÂ testÂ wasÂ performedÂ toÂ determineÂ theÂ  OddsÂ  ratio,Â  whileÂ  bivariate,Â  multivariate,Â  andÂ  logisticÂ  regressionÂ  analysesÂ  wereÂ performedÂ  toÂ  determineÂ  theÂ  contributionÂ  ofÂ  eachÂ  parameterÂ  toÂ  theÂ  developmentÂ  ofÂ recurrentÂ UTI.Â Results:Â  TwoÂ  hundredÂ  pediatricÂ  cases,Â  whichÂ  consistedÂ  ofÂ  101Â  (50.5%)Â  malesÂ  andÂ  99Â (49.5%)Â females,Â withÂ recurrentÂ UTIÂ wereÂ involvedÂ inÂ theÂ presentÂ study.Â FiftyÂ (50%)Â casesÂ withoutÂ prophylacticÂ antibioticsÂ developedÂ recurrentÂ UTIÂ (OR,Â 2.57